2016
DOI: 10.1093/bib/bbw086
|View full text |Cite
|
Sign up to set email alerts
|

Transferring entropy to the realm of GxG interactions

Abstract: Genome-wide association studies are moving to genome-wide interaction studies, as the genetic background of many diseases appears to be more complex than previously supposed. Thus, many statistical approaches have been proposed to detect gene–gene (GxG) interactions, among them numerous information theory-based methods, inspired by the concept of entropy. These are suggested as particularly powerful and, because of their nonlinearity, as better able to capture nonlinear relationships between genetic variants a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 54 publications
0
16
0
Order By: Relevance
“…This modification increased the runtime of PLINK by a factor of about 5.7, but the results were almost exactly equal now, showing that the inconsistencies were caused by the different precisions. We believe the remaining small inconsistencies were due to numerical problems in PLINK when accumulating small floating-point values over all samples in steps 2 and 3 of computing the logistic regression test (see (5) and (6) in Sect. 2.1).…”
Section: Performance Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…This modification increased the runtime of PLINK by a factor of about 5.7, but the results were almost exactly equal now, showing that the inconsistencies were caused by the different precisions. We believe the remaining small inconsistencies were due to numerical problems in PLINK when accumulating small floating-point values over all samples in steps 2 and 3 of computing the logistic regression test (see (5) and (6) in Sect. 2.1).…”
Section: Performance Evaluationmentioning
confidence: 99%
“…Recently, entropy-based measures for GxG interaction detection gained increasing attention. A well-written overview can be found in [5].…”
Section: Introductionmentioning
confidence: 99%
“…This concept is modelfree and measures the uncertainty or disorder in a system and could therefore lend itself to detect interactions for many genotype constellations. This technique is suggested as particularly powerful and, because of the nonlinearity, as better able to capture nonlinear relationships between genetic variants or other variables [18]. Ferrario et al reviewed different entropy-based measures providing information on suggested test statistics, simulations and implementations [18].…”
Section: Introductionmentioning
confidence: 99%
“…This technique is suggested as particularly powerful and, because of the nonlinearity, as better able to capture nonlinear relationships between genetic variants or other variables [18]. Ferrario et al reviewed different entropy-based measures providing information on suggested test statistics, simulations and implementations [18]. Focusing on second order interaction, there are three important concepts, namely conditional mutual information, information gain, and relative information gain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation